2009
DOI: 10.1111/j.1439-0272.2008.00884.x
|View full text |Cite
|
Sign up to set email alerts
|

Fertilisation and pregnancy outcome after ICSI in globozoospermic patients without assisted oocyte activation

Abstract: The successful outcome of intracytoplasmic sperm injection (ICSI) with globozoospermic sperm and non-activated oocytes is reported. Three couples underwent ICSI treatment and two of the patients were siblings. Forty-four non-activated oocytes were injected, 26 oocytes fertilised normally and 17 good quality embryos were obtained. Six embryo transfers were carried out, three with fresh embryos and three with frozen-thawed embryos. Three pregnancies resulted from the fresh embryo transfers and additionally two p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 17 publications
(21 reference statements)
0
13
1
Order By: Relevance
“…Progesterone was administered daily vaginally from the day of oocyte retrieval until the time of a negative pregnancy test or until 8 weeks of gestation. Embryo cryopreservation and frozen/thawed embryo transfer were performed as described previously [28]. …”
Section: Methodsmentioning
confidence: 99%
“…Progesterone was administered daily vaginally from the day of oocyte retrieval until the time of a negative pregnancy test or until 8 weeks of gestation. Embryo cryopreservation and frozen/thawed embryo transfer were performed as described previously [28]. …”
Section: Methodsmentioning
confidence: 99%
“…Based on this evidence and introduction of intracytoplasmic sperm injection (ICSI) into assisted reproductive techniques, a window of hope was opened for this type of infertile men. But unfortunately, rate fertilisation following ICSI was futile in these cases (Bechoua, Chiron, Delcleve‐Paulhac, Sagot, & Jimenez,; Dirican, Isik, Vicdan, Sozen, & Suludere, ; Zhang, Long, Huang, Xin, & Wu, ). In this regard, several studies demonstrated assisted oocyte activation (AOA) technique following ICSI can overcome this dearth.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the condition was considered intractable until the introduction of intracytoplasmic sperm injection (ICSI). A normal live birth has been achieved by ICSI with globozoospermic sperm (2)(3)(4)(5); however, there are a significant number of patients in whom ICSI fails completely because of limited or failed fertilization. Fertilization failures have been attributed to the defective ability of the roundheaded sperm to activate oocytes (6).…”
mentioning
confidence: 98%